Aktivisme Pergerakan Mahasiswa Islam Indonesia (PMII) dalam Dinamika Reformasi di Kota Medan, 1998–1999 - Sembiring, Annisa Almadhani br; Achiriah, Achiriah (Local History & Heritage, 2025)
This study examines the role of the Indonesian Islamic Student Movement (PMII) Medan Branch in the Reformasi movement of 1998–1999, a pivotal moment in Indonesia’s democratic transition. While previous scholarship has predominantly centered on student activism in Jakarta, this research addresses the relative neglect of regional dynamics, particularly the contributions of PMII in Medan. Utilizing a qualitative approach and case study method, the research draws on in-depth interviews with three key activists who were directly involved in the reform movement. The findings reveal that PMII Medan played a significant role in mobilizing mass demonstrations, conducting political education, building inter-organizational networks, and engaging in policy advocacy. These strategies illustrate the characteristics of a critical-transformative movement, emphasizing collective consciousness, organizational resilience, and strategic collaboration. The study underscores that regional student organizations such as PMII Medan were not peripheral actors, but integral agents in shaping Indonesia’s national reform agenda. These insights contribute to a more nuanced understanding of local agency within the broader historiography of Indonesian democratization.